A transcultural media facet by the playwright Martins Pena - Gimenez, Priscila Renata (Revista de Letras, 2014)
Commonly known as the creator of the Brazilian comedy, Martins Pena served as a journalist for Jornal do Commercio. In this newspaper, between 1846- 1847, Pena was the creator of the captions for the theatrical serials entitled “Semana Lírica”. Following the trend of “media revolution” triggered with the creation of the French newspaper La Presse in 1836, we will work with the hypothesis that such captions are a cultural trait transferred to the footer of the Brazilian newspaper. However, if we think of the “media globalization” process occurred throughout the nineteenth century, in which are inscribed the internationalization of journalistic models, not only the captions in question, but also the very facet of Martins Pena as their creator can be thought of as a manifestation of the communication and circulation of ideas, as well as exchanges between two different cultural spaces. Therefore, based on the studies of literature and the press and in the theory of Cultural Transfers, we intend to reflect on this issue explaining the route of the journalist and comedy writer and how he can be considered a theatrical serial playwright. We conclude by exploring how Pena sees himself as a serial writer, retracing his comments on his role, recovered in his chronicles.